Comparatives Revisited: Downward-Entailing Differentials Do Not Threaten Encapsulation Theories - Zhang, Linmin; Ling, Jia (Proceedings of the Amsterdam Colloquium, 2015)
We analyze comparative morphemes (e.g.,-er, more) as intervals of type ⟨dt⟩ that serve as differentials in comparatives. We propose that comparatives are about the distance between two intervals on a scale: the differential, which is an interval, is the result of subtracting the interval representing the position of the comparative standard on a scale from the interval representing the position of the comparative subject. We show that our analysis has at least two advantages. First, it accounts for the semantics of comparatives with downward-entailing or non-monotone differentials in a very natural way, without relying on any strategy that essentially makes quantifiers inside of the than-clause take scope over the matrix clause. Second, it opens up new possibilities to give a unified account for various uses of comparative morphemes (e.g., the more, comparative correlatives, etc). We mainly focus on the first advantage in this paper.